Implementasi Ekstrakurikuler Tilawah dalam Membangun Karakter Siswa di MA Syarifuddin Lumajang - Risviyah, Nadhifatur; Nusyamsiyah, Siti; Huda, Hairul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2025)
Character education is one of the important aspects of the education system that aims to shape students' personalities so that they have good morals and become individuals with integrity. One method that can be used in shaping students' characters is through extracurricular activities, particularly reciting the Qur'an. This study aims to determine how extracurricular activities involving reciting the Qur'an can play a role in building the characters of students at MA Syarifuddin Lumajang. The research method used in this study is a qualitative approach with a descriptive research design. Data collection techniques include observation, interviews, and documentation. The research subjects are the extracurricular recitation instructors and several students participating in the activity. Data analysis employs triangulation of sources to verify and evaluate the validity of data or information obtained from primary informants. The research results indicate that the tilawah extracurricular activity is conducted through several stages, such as basic tilawah instruction (tajwid, makhraj huruf), regular practice, and mental and spiritual development. This activity has a positive impact on students' character, such as fostering discipline, responsibility, religiosity, and self-confidence.